Sistem Pengambilan Keputusan Pemilihan Bibit Ikan Air Tawar untuk Dibudidayakan Menggunakan Metode AHP Berbasis Web - Jumarlis, Mila (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
Farmers in fish farming in the context of selecting suitable fish seeds for cultivation have not paid too much attention to geographical conditions and water quality. The purpose of this study is to assist freshwater fish farming farmers in selecting the types of fish seeds to be cultivated in accordance with geographical conditions and quality. water in the area. The method used is the AHP method, where the AHP method is a functional hierarchy with the main input being human perception. With a hierarchy, a complex and unstructured problem is solved into groups arranged into a hierarchical form. The research design used is UML (Unified Modeling Language), which is designed in a structured manner consisting of usecase diagrams, activity diagrams, sequence diagrams and class diagrams. The language used in building this system is the PHP programming language with a sublime text editor and using the xampp database. The results of this study are a Freshwater Fish Seed Selection Decision Making System that can make it easier for farmers to make decisions in selecting fish seeds.